Acrylate polyurethane coating for ship anticorrosion and preparation method thereof
Patent Information
- Application Number
- CN202610977057.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]上述方案将对氨基二苯胺防老剂接枝于改性丁苯橡胶胶乳并插层至氧化石墨烯片层中,以提升橡胶耐老化性,但在海洋或高湿热环境中,对氨基二苯胺的氨基和亚氨基易发生质子化,削弱其与环氧基团的键合能力,且接枝产物在水分子渗透下逐渐水解解吸,导致防老剂从橡胶纳米粒子表面迁移流失,造成局部防老功能丧失,进而使丁苯橡胶在紫外光与湿热协同作用下加速交联硬化或断链,最终导致涂层长期柔韧性、抗冲击性及耐候性能显著下降
1、本发明通过没食子酸插层锌铝镧水滑石粉末、聚多巴胺包覆及氨基化碳化复合粉体的多重协同设计,进一步提升涂层的防腐性能。其中水滑石层间的没食子酸根可释放缓蚀阴离子形成钝化膜,镧离子掺杂增强对氯离子的交换捕获能力,聚多巴胺包覆改善填料分散性与界面结合力,使附着力大幅提高,而氨基化碳化复合粉体作为刚性骨架并提供碳层物理屏障,与聚多巴胺形成三维交联网络,有效阻隔水、氧和电解质的渗透。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane coating technology, specifically relating to an acrylic polyurethane coating for ship corrosion protection and its preparation method. Background Technology
[0002] Acrylic polyurethane coatings are two-component high-performance protective coatings composed of hydroxyl acrylic resin, isocyanate curing agent, functional fillers and additives. They combine the excellent weather resistance of acrylic resin with the strong adhesion and high toughness of polyurethane resin, making them the mainstream long-lasting protective topcoat in the marine industry.
[0003] In the marine operating environment, this coating is exposed to harsh marine conditions for a long time, constantly subjected to strong ultraviolet radiation, salt spray corrosion, and continuous scouring by waves, sea wind and dust friction. During the ship's voyage, it will also experience mechanical collisions and surface wear, which places extremely high demands on the protective performance of the ship's paint surface. To adapt to the harsh marine working conditions, the industry usually adds nano-functional fillers and special modifying additives to give the coating stronger practical performance in terms of salt spray resistance, aging resistance, wear resistance and impact resistance.
[0004] Chinese invention patent application CN121271400A discloses an acrylic polyurethane coating containing modified graphene and its preparation method. The method involves preparing a modified styrene-butadiene rubber latex through free radical copolymerization of liquid polybutadiene, p-aminostyrene, and glycidyl methacrylate. Then, p-aminodiphenylamine reacts with the epoxy groups in the latex to undergo a ring-opening reaction, yielding an anti-aging modified styrene-butadiene rubber latex. This latex is then mixed with graphene oxide and trimethylolpropane triacrylate and irradiated to allow rubber nanoparticles to be intercalated in situ into the graphene oxide sheets, forming intercalated modified graphene. Simultaneously, vinyl-modified titanium dioxide powder is prepared by reacting titanium dioxide with isophorone diisocyanate and hydroxyethyl methacrylate. Finally, the intercalated modified graphene, hydroxyethyl methacrylate, butyl acrylate, and diphenylmethane diisocyanate are reacted to generate an acrylic grafted polyurethane copolymer, which is then copolymerized with the vinyl-modified titanium dioxide powder to obtain the acrylic polyurethane coating containing modified graphene.
[0005] The above scheme grafts p-aminodiphenylamine antioxidant onto modified styrene-butadiene rubber latex and intercalates it into graphene oxide sheets to improve the aging resistance of rubber. However, in marine or high-humidity and heat environments, the amino and imino groups of p-aminodiphenylamine are prone to protonation, weakening their bonding ability with epoxy groups. Furthermore, the grafted product is gradually hydrolyzed and desorbed under the penetration of water molecules, causing the antioxidant to migrate and be lost from the surface of rubber nanoparticles, resulting in the loss of local anti-aging function. Consequently, under the synergistic effect of ultraviolet light and humid heat, the styrene-butadiene rubber is accelerated to crosslink harden or break chains, ultimately leading to a significant decrease in the long-term flexibility, impact resistance, and weather resistance of the coating. Summary of the Invention
[0006] The purpose of this invention is to provide an acrylic polyurethane coating for ship corrosion protection and its preparation method. By using gallic acid as an antioxidant, it is intercalated between zinc-aluminum-lanthanum hydrotalcite layers. The strong electrostatic interaction between the positive charge of the layer and the gallic acid anion stabilizes and confines it in the nanoscale domain, effectively inhibiting its migration and loss in humid environments. Furthermore, by coating the surface with dopamine, the long-term fixation of the antioxidant is further enhanced and the filler is given excellent interfacial adhesion, thereby effectively solving the problem of easy migration and degradation of anti-aging components.
[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing an acrylic polyurethane coating for ship corrosion protection includes the following steps: Step 1: Zinc, aluminum, and lanthanum nitrates are co-precipitated with gallic acid under alkaline conditions and then hydrothermally crystallized to obtain gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder. This powder is then subjected to oxidative self-polymerization to obtain dopamine-coated gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder.
[0008] Step 2: Attapulgite is hydrothermally carbonized with glucose and tannic acid, and then aminated to obtain aminated carbonized composite powder.
[0009] Step 3: Add xylene to the grinding slurry to make a composite filler slurry, and mix it with the tinting paint slurry, xylene, and polyurethane curing agent to obtain an acrylic polyurethane coating for ship corrosion protection.
[0010] Furthermore, the grinding slurry is obtained by mixing dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder, aminated carbonized composite powder, xylene and dispersant BYK-110 in a mass ratio of 180-195:90-100:180-190:5.4-6.2 and grinding to a fineness ≤25μm.
[0011] Furthermore, the specific preparation method of gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder is as follows: Under nitrogen protection, the mixed salt solution and mixed alkali solution were placed in constant pressure dropping funnels and simultaneously added to a three-necked flask using a double-drop method. The dropping rate was controlled to maintain the pH of the reaction system at 10±0.5. After the addition was complete, the mixture was stirred in a water bath at 80-85℃ for 20-24 hours, then transferred to a high-pressure reactor and hydrothermally crystallized at 180-190℃ for 8-10 hours. After natural cooling, the mixture was filtered, and the product was washed multiple times until the filtrate was neutral. The product was then dried to constant weight to obtain gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder.
[0012] Furthermore, the mixed salt solution is obtained by mixing zinc nitrate hexahydrate, aluminum nitrate nonahydrate, lanthanum nitrate hexahydrate, and deionized water in a ratio of 288.2-305.4g: 165-182g: 19.14-25.36g: 2.2-2.8L.
[0013] Furthermore, the mixed alkaline solution is obtained by mixing 13.8 wt% sodium hydroxide solution and 10.6 wt% gallic acid solution at a volume ratio of 1.1-1.3 L : 1.1-1.5 L.
[0014] Furthermore, the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1.
[0015] Furthermore, the specific preparation method of dopamine-coated gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder is as follows: Gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder was added to Tris-HCl buffer at pH 8.5, sonicated for 15-25 min, dopamine hydrochloride was added, stirred for 24-26 h, filtered, the product was washed, and vacuum dried to constant weight to obtain dopamine-coated gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder.
[0016] Furthermore, the ratio of gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder, Tris-HCl buffer, and dopamine hydrochloride is 180-200g: 18-19.5L: 18-22g.
[0017] Furthermore, the specific preparation method of the amination-carbonization composite powder is as follows: Add attapulgite, glucose, and tannic acid to deionized water, sonicate for 15-25 min, add ethylenediamine dropwise under stirring to adjust the pH to 11, transfer to a high-pressure reactor, and hydrothermally react at 180-190℃ for 48-50 h. After naturally cooling to room temperature, centrifuge and filter, wash the product, dry it to constant weight by forced air, grind it, and sieve it to obtain aminated carbonized composite powder.
[0018] Furthermore, the ratio of attapulgite, glucose, tannic acid, and deionized water is 90-100g: 270-280g: 45-50g: 4.5-5.2L.
[0019] Furthermore, the specific preparation method of the composite filler slurry is as follows: Add xylene to the grinding slurry, stir for 10-20 minutes, filter and discharge to obtain composite filler slurry.
[0020] Furthermore, the mass ratio of xylene to grinding slurry is 184.6-196.4:455.4-491.2.
[0021] Furthermore, the specific preparation method of the acrylic polyurethane coating for ship corrosion protection is as follows: Add xylene to the tinted paint slurry to adjust the viscosity to 100±5 KU at 25℃, pass it through a 200-mesh sieve to obtain the main paint. Before use, add polyurethane curing agent and stir evenly to obtain an acrylic polyurethane coating for ship corrosion protection.
[0022] Furthermore, the mass ratio of tinted paint paste, xylene, and polyurethane curing agent is 990-1026:10-14:200-210.
[0023] Furthermore, the tinted paint paste is obtained by mixing xylene, hydroxyl acrylic resin, white paste, composite filler paste, 3-5g dispersant BYK2150, black paste, medium yellow paste and blue paste in a mass ratio of 17-21:130-135:200-215:640-650:3-5:0.3-0.5:0.1-0.18:0.05-0.1.
[0024] The beneficial effects of this invention are: 1. This invention further enhances the corrosion resistance of the coating through a multi-layered synergistic design of gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder, polydopamine coating, and aminated carbonized composite powder. Specifically, the gallic acid ions between the hydrotalcite layers release corrosion-inhibiting anions to form a passivation film; lanthanum ion doping enhances the exchange and capture capacity for chloride ions; polydopamine coating improves filler dispersibility and interfacial bonding, significantly increasing adhesion; and the aminated carbonized composite powder acts as a rigid framework and provides a physical barrier to the carbon layer, forming a three-dimensional cross-linked network with polydopamine, effectively blocking the penetration of water, oxygen, and electrolytes.
[0025] The overall process is compatible with existing coating production equipment, the raw materials are readily available, and the resulting coating has excellent salt spray resistance, strong adhesion, and high shielding durability, fully meeting the requirements of long-term effectiveness and construction adaptability for marine anti-corrosion coating.
[0026] 2. The dopamine-coated gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder of this invention features gallic acid intercalation that expands the interlayer spacing of the hydrotalcite and endows it with chloride ion exchange and corrosion inhibitor release capabilities. Lanthanum ion doping enhances the electrostatic capture of chloride ions and forms a passivation deposition layer. The polydopamine shell not only improves the dispersibility of the filler in the resin but also chemically crosslinks with the metal substrate, resin, and aminated carbide attapulgite through groups such as catechol, forming a three-dimensional network structure. This allows the filler to actively capture corrosive chloride ions and release gallic acid ions as needed to chelate and passivate the metal surface, while also significantly improving adhesion. Furthermore, it synergistically forms a dense physical shielding layer with the aminated carbide composite powder, increasing the actual protective performance.
[0027] 3. The aminated carbonized composite powder of this invention is prepared by a synergistic hydrothermal reaction of attapulgite, glucose, tannic acid and ethylenediamine. Attapulgite serves as a rigid rod-shaped framework, providing mechanical support for the composite powder and preventing the stacking of hydrotalcite layers. The carbon layer formed by the dehydration and carbonization of glucose uniformly coats the surface of attapulgite, forming a dense physical barrier that effectively blocks the penetration of water, oxygen and chloride ions. Tannic acid participates in the carbonization reaction as a co-carbonizing agent, introducing a large number of phenolic hydroxyl groups, which enhances the hydrogen bonding and π-π stacking effect between the carbon layer and the polydopamine-coated hydrotalcite. Ethylenediamine is aminated in situ during the hydrothermal process, making the surface of the carbon layer rich in amino groups, which can undergo Michael addition reaction with the quinone groups of polydopamine to form stable covalent crosslinks.
[0028] The rod-shaped morphology of attapulgite, together with the carbon layer, constructs a core-shell structure with a rigid framework and a flexible carbon shell, avoiding the agglomeration of single carbon materials. The abundant surface functional groups enable it to chemically bond efficiently with polydopamine-coated hydrotalcite, forming a three-dimensional cross-linked network. This significantly improves the dispersibility of the filler in the resin and the density of the coating. At the same time, the hydrophobic properties and physical barrier of the carbon layer, combined with the labyrinth effect of attapulgite, further extend the diffusion path of corrosive media, forming a dual anti-corrosion mechanism with the active corrosion inhibition function of hydrotalcite in the system. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments in the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1: A method for preparing an acrylic polyurethane coating for ship corrosion protection, comprising the following steps: S1: Dissolve 288.2 g zinc nitrate hexahydrate, 165 g aluminum nitrate nonahydrate, and 19.14 g lanthanum nitrate hexahydrate in 2.2 L of deionized water to obtain a mixed salt solution; add 1.1 L of 13.8 wt% sodium hydroxide solution and 1.1 L... A 10.6 wt% gallic acid solution was mixed thoroughly to obtain a mixed alkaline solution. Under nitrogen protection, 2.2 L of the mixed salt solution and 2.2 L of the mixed alkaline solution were placed in constant pressure dropping funnels and simultaneously added to a three-necked flask using a double-drop method. The dropping rate was controlled to maintain the pH of the reaction system at 9.5. After the addition was complete, the mixture was stirred in an 80℃ water bath for 20 h, then transferred to a high-pressure reactor and hydrothermally crystallized at 180℃ for 8 h. After natural cooling, the mixture was filtered, and the solid product was collected. The product was washed several times with deionized water until the filtrate was neutral, and then dried at 80℃ for 12 h to obtain gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder with a particle size of approximately 120 nm.
[0031] During the co-precipitation process, zinc and aluminum ions form intercalated layered double hydroxides with gallate ions. Lanthanum ions, through surface complexation and interlayer ion exchange, work together to anchor lanthanum ions on the surface of the intercalated layered double hydroxides and at interlayer edge sites, providing additional thermal stabilization.
[0032] S2: 180g of gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder was added to 18L of Tris-HCl buffer solution with a pH of 8.5. After ultrasonic dispersion for 15min, 18g of dopamine hydrochloride was added. The mixture was stirred at room temperature for 24h, filtered, and the solid product was collected. The product was washed three times each with anhydrous ethanol and deionized water, and then vacuum dried at 50℃ for 12h to obtain dopamine-coated gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder with a coating layer of about 5nm.
[0033] Dopamine hydrochloride undergoes auto-oxidative polymerization in Tris-HCl buffer at pH 8.5. The resulting polydopamine interacts with the active sites on the surface of gallic acid-intercalated zinc aluminum lanthanum hydrotalcite through groups such as catechol, thereby forming a uniform coating layer in situ.
[0034] S3: Add 90g of attapulgite, 270g of glucose and 45g of tannic acid to 4.5L of deionized water, sonicate for 15min, add ethylenediamine dropwise under stirring to adjust the pH to 11, transfer to a high-pressure reactor, hydrothermally react at 180℃ for 48h, cool naturally to room temperature, centrifuge at 8000rpm for 10min, filter, collect the solid product, wash the product three times each with anhydrous ethanol and deionized water, dry in a forced-air environment at 80℃ for 12h, grind, and pass through a 200-mesh sieve to obtain anamine-carbonized composite powder with a particle size of approximately 600nm.
[0035] Under alkaline hydrothermal conditions, glucose is dehydrated and carbonized to form a carbon layer, which is then loaded onto the surface of attapulgite. Simultaneously, the amino group provided by ethylenediamine undergoes a nucleophilic addition-elimination reaction (Schiff base reaction) with the aldehyde, carbonyl, and other oxygen-containing groups in the carbon layer to form C=N bonds, thereby achieving one-step amination. Tannic acid participates in the carbonization reaction as a co-carbonizing agent, additionally introducing phenolic hydroxyl groups.
[0036] S4: Add 180g of dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder and 90g of aminated carbonized composite powder to 180g of xylene, add 5.4g of dispersant BYK-110, disperse at 1500rpm for 40min, transfer to a sand mill, grind to a fineness ≤25μm to obtain a grinding slurry; add 184.6g of xylene to 455.4g of grinding slurry, continue stirring for 10min, filter and discharge to obtain a composite filler slurry.
[0037] S5: Add 17g xylene, 130g hydroxyl acrylic resin, 200g white paste, 640g composite filler paste and 3g dispersant BYK2150 to a dispersion tank, stir at 500rpm for 20min, grind to fineness ≤25μm to obtain base paint, then add 0.3g black paste, 0.1g medium yellow paste and 0.05g blue paste, stir evenly until the color meets RAL7035 standard (color difference △E≤0.3) to obtain tinting paint paste; add 10g xylene to 990g tinting paint paste to adjust the viscosity to 95KU at 25℃, pass through a 200-mesh sieve to obtain the main paint, add 200g polyurethane curing agent before use, stir evenly to obtain acrylate polyurethane coating for marine anti-corrosion.
[0038] Example 2: A method for preparing an acrylic polyurethane coating for ship corrosion protection, comprising the following steps: S1: Dissolve 296.8 g zinc nitrate hexahydrate, 173.5 g aluminum nitrate nonahydrate, and 22.25 g lanthanum nitrate hexahydrate in 2.5 L of deionized water to obtain a mixed salt solution; add 1.2 L of 13.8 wt% sodium hydroxide solution and 1.3 L of... A 10.6 wt% gallic acid solution was mixed thoroughly to obtain a mixed alkaline solution. Under nitrogen protection, 2.5 L of the mixed salt solution and 2.5 L of the mixed alkaline solution were placed in constant pressure dropping funnels and simultaneously added to a three-necked flask using a double-drop method. The dropping rate was controlled to maintain the pH of the reaction system at 10. After the addition was complete, the mixture was stirred in a water bath at 82.5 °C for 22 h. The mixture was then transferred to a high-pressure reactor and hydrothermally crystallized at 185 °C for 9 h. After natural cooling, the mixture was filtered, and the solid product was collected. The product was washed repeatedly with deionized water until the filtrate was neutral. The product was then dried at 85 °C for 13 h to obtain gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder with a particle size of approximately 135 nm.
[0039] S2: 190g of gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder was added to 18.75L of Tris-HCl buffer solution with a pH of 8.5. After ultrasonic dispersion for 20min, 20g of dopamine hydrochloride was added. The mixture was stirred at room temperature for 25h, filtered, and the solid product was collected. The product was washed four times each with anhydrous ethanol and deionized water, and then vacuum dried at 55℃ for 13h to obtain dopamine-coated gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder with a coating layer of about 6.5nm.
[0040] S3: Add 95g of attapulgite, 275g of glucose and 47.5g of tannic acid to 4.85L of deionized water, sonicate for 20min, add ethylenediamine dropwise under stirring to adjust the pH to 11, transfer to a high-pressure reactor, hydrothermally react at 185℃ for 49h, cool naturally to room temperature, centrifuge at 9000rpm for 12.5min, filter, collect the solid product, wash the product four times each with anhydrous ethanol and deionized water, dry in a forced-air environment at 85℃ for 13h, grind, and pass through a 200-mesh sieve to obtain an aminated carbonized composite powder with a particle size of approximately 700nm.
[0041] S4: Add 187.5g of dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder and 95g of aminated carbonized composite powder to 185g of xylene, add 5.8g of dispersant BYK-110, disperse at 1650rpm for 45min, transfer to a sand mill, grind to a fineness ≤25μm to obtain a grinding slurry; add 190.5g of xylene to 473.3g of grinding slurry, continue stirring for 15min, filter and discharge to obtain a composite filler slurry.
[0042] S5: Add 19g xylene, 132.5g hydroxyl acrylic resin, 207.5g white paste, 645g composite filler paste, and 4g dispersant BYK2150 to a dispersion tank, stir at 550rpm for 25min, and grind to a fineness ≤25μm to obtain the base paint. Then add 0.4g black paste, 0.14g medium yellow paste, and 0.075g blue paste, and stir until the color meets the RAL7035 standard (color difference △E≤0.3) to obtain the tinting paint paste. Add 12g xylene to 1008g of tinting paint paste to adjust the viscosity to 100KU at 25℃, and pass through a 200-mesh sieve to obtain the main paint. Before use, add 205g of polyurethane curing agent and stir until uniform to obtain the acrylic polyurethane coating for marine corrosion protection.
[0043] Example 3: A method for preparing an acrylic polyurethane coating for ship corrosion protection, comprising the following steps: S1: Dissolve 305.4 g zinc nitrate hexahydrate, 182 g aluminum nitrate nonahydrate, and 25.36 g lanthanum nitrate hexahydrate in 2.8 L of deionized water to obtain a mixed salt solution; add 1.3 L of 13.8 wt% sodium hydroxide solution and 1.5 L of... A 10.6 wt% gallic acid solution was mixed thoroughly to obtain a mixed alkaline solution. Under nitrogen protection, 2.8 L of the mixed salt solution and 2.8 L of the mixed alkaline solution were placed in constant pressure dropping funnels and simultaneously added to a three-necked flask using a double-drop method. The dropping rate was controlled to maintain the pH of the reaction system at 10.5. After the addition was complete, the mixture was stirred in an 85℃ water bath for 24 h, then transferred to a high-pressure reactor and hydrothermally crystallized at 190℃ for 10 h. After natural cooling, the mixture was filtered, and the solid product was collected. The product was washed repeatedly with deionized water until the filtrate was neutral, and then dried at 90℃ for 14 h to obtain gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder with a particle size of approximately 150 nm.
[0044] S2: 200g of gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder was added to 19.5L of Tris-HCl buffer solution with a pH of 8.5. After ultrasonic dispersion for 25min, 22g of dopamine hydrochloride was added. The mixture was stirred at room temperature for 26h, filtered, and the solid product was collected. The product was washed 5 times each with anhydrous ethanol and deionized water, and then vacuum dried at 60℃ for 14h to obtain dopamine-coated gallic acid-intercalated zinc aluminum lanthanum hydrotalcite powder with a coating layer of about 8nm.
[0045] S3: Add 100g attapulgite, 280g glucose and 50g tannic acid to 5.2L deionized water, sonicate for 25min, add ethylenediamine dropwise under stirring to adjust the pH to 11, transfer to a high-pressure reactor, hydrothermally react at 190℃ for 50h, cool naturally to room temperature, centrifuge at 10000rpm for 15min, filter, collect the solid product, wash the product 5 times each with anhydrous ethanol and deionized water, dry in a forced-air environment at 90℃ for 14h, grind, and pass through a 200-mesh sieve to obtain anamine-carbonized composite powder with a particle size of approximately 800nm.
[0046] S4: Add 195g of dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder and 100g of aminated carbonized composite powder to 190g of xylene, add 6.2g of dispersant BYK-110, disperse at 1800rpm for 50min, transfer to a sand mill, grind to a fineness ≤25μm to obtain a grinding slurry; add 196.4g of xylene to 491.2g of grinding slurry, continue stirring for 20min, filter and discharge to obtain a composite filler slurry.
[0047] S5: Add 21g xylene, 135g hydroxyl acrylic resin, 215g white paste, 650g composite filler paste and 5g dispersant BYK2150 to a dispersion tank, stir at 600rpm for 30min, grind to fineness ≤25μm to obtain base paint, then add 0.5g black paste, 0.18g medium yellow paste and 0.1g blue paste, stir evenly until the color meets RAL7035 standard (color difference △E≤0.3) to obtain tinting paint paste; add 14g xylene to 1026g tinting paint paste to adjust the viscosity to 105KU at 25℃, pass through a 200-mesh sieve to obtain the main paint, add 210g polyurethane curing agent before use, stir evenly to obtain acrylate polyurethane coating for marine anti-corrosion.
[0048] RAL7035 is a standard color (industrial gray) in the German RAL color chart. It is a soft light gray commonly used for painting industrial equipment, machinery and ships. Its typical RGB value is approximately (208, 208, 208).
[0049] In Examples 1-3, zinc nitrate hexahydrate was selected from Hubei Rishengchang New Material Technology Co., Ltd., CAS No. 10196-18-6; aluminum nitrate nonahydrate was selected from Wuhan Jixin Yibang Biotechnology Co., Ltd., CAS No. 7784-27-2; lanthanum nitrate hexahydrate was selected from Hubei Shuaiyan Ligao Biomedical Co., Ltd., CAS No. 100587-94-8; Tris-HCl buffer was selected from Nanjing Anxinchang Technology Co., Ltd., model PHC002; dopamine hydrochloride was selected from Shanghai Zheyan Biotechnology Co., Ltd., CAS No. 62-31-7; attapulgite was selected from Lingshou County Zhanteng Mineral Products Processing Plant, mesh size 120-325; glucose was selected from Zibo Ruixue Sugar Industry Co., Ltd., CAS No. 50-99-7; tannic acid was selected from... The raw materials are sourced from Hubei Shineng Chemical Technology Co., Ltd. (CAS No. 1401-55-4); xylene from Dongguan Zhengyangming New Materials Co., Ltd. (CAS No. 1330-20-7); dispersant BYK-110 from Shanghai Qizhan New Materials Technology Co., Ltd.; hydroxy acrylic resin from Nantong Fangxin Chemical Co., Ltd. (model FX-9024); white paste from Suzhou Aolaixin Building Materials Co., Ltd.; dispersant BYK2150 from Shanghai Puhao Chemical Co., Ltd.; black paste from Suzhou Aolaixin Building Materials Co., Ltd. (model JL-SX); medium yellow paste from Suzhou Aolaixin Building Materials Co., Ltd. (model JL-NR); blue paste from Changzhou Qiushuo Chemical Co., Ltd.; and polyurethane curing agent from Sanmu Group (model 730SU). All other raw materials are commercially available products.
[0050] Comparative Example 1: The difference from Example 1 is that lanthanum nitrate hexahydrate is not added in step S1, the total volume of the mixed salt solution is kept at 2.2L, and the volume reduced due to the lack of lanthanum nitrate is made up with deionized water to obtain gallic acid intercalated zinc aluminum hydrotalcite powder. In step S2, the gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder is replaced with gallic acid intercalated zinc aluminum hydrotalcite powder, and the other steps remain unchanged to obtain an acrylic polyurethane coating for ship corrosion protection.
[0051] Comparative Example 2: The difference from Example 1 is that in step S1, 10.6 wt% gallic acid solution is not added, but an equal volume of deionized water is used instead to obtain zinc aluminum lanthanum hydrotalcite powder. In step S2, the gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder is replaced with zinc aluminum lanthanum hydrotalcite powder, and the other steps remain unchanged to obtain an acrylic polyurethane coating for ship corrosion protection.
[0052] Comparative Example 3: The difference from Example 1 is that step S2 is omitted, and the dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder in step S4 is replaced with gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder. The remaining steps remain unchanged, resulting in an acrylic polyurethane coating for ship corrosion protection.
[0053] Comparative Example 4: The difference from Example 1 is that tannic acid is not added in step S3 to obtain carbonized composite powder, and the aminated carbonized composite powder in step S4 is replaced with carbonized composite powder, while the other steps remain unchanged to obtain an acrylic polyurethane coating for ship corrosion protection.
[0054] Comparative Example 5: The difference from Example 1 is that step S3 is omitted, and the aminated carbonized composite powder in step S4 is replaced with commercially available attapulgite. The remaining steps remain unchanged, resulting in an acrylic polyurethane coating for marine corrosion protection.
[0055] The following performance tests were conducted on the acrylic polyurethane coatings for ship corrosion protection prepared in Examples 1-3 and Comparative Examples 1-5: Salt spray resistance test: The test is conducted in accordance with GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test". The testing instrument is a salt spray test chamber. The neutral salt spray test method is adopted. The coating of marine anti-corrosion acrylic polyurethane coating with a dry film thickness of 300μm (single coating, no primer) is scratched through to the substrate with a scratch knife. The scratch length is about 50mm. Then it is placed in a continuous spray environment of 5% NaCl solution at a temperature of 35℃ and a pH value of 6.5-7.2. After 1000h, it is taken out and the rust spread width at the scratch is observed. The smaller the value, the better the long-term corrosion resistance of the coating.
[0056] Adhesion: The adhesion was tested according to GB / T 5210-2006 "Paints and Varnishes - Pull-off Test". The testing instrument was an adhesion tester. The test column was bonded to the surface of the coating with epoxy adhesive and the coating with acrylate polyurethane coating for marine anti-corrosion. After curing for 24 hours, it was pulled off vertically at a tensile speed of 10 mm / min. The separation strength between the coating and the substrate was measured. The higher the value, the stronger the interfacial bonding force.
[0057] The substrate is a carbon steel plate that has been sandblasted to grade 2.5, with a surface roughness of 50-70μm.
[0058] Electrochemical impedance spectroscopy (EIS): The EIS was measured using a standard electrochemical testing method. The instrument used was a Chi660e electrochemical workstation with a three-electrode system (an aluminum substrate coated with a 250 μm thick dry film of marine corrosion-resistant acrylic polyurethane coating served as the working electrode, with an exposed area of approximately 10 cm²). 2 A saturated calomel electrode was used as the reference electrode, and a platinum electrode as the auxiliary electrode, with a 3.5 wt% NaCl solution as the electrolyte. After the open-circuit potential stabilized, EIS testing was performed, with the impedance test frequency variation range being 10 Hz. -2 -10 5 With a signal amplitude of 10mV and a frequency of Hz, measure the impedance value |Z| at a low frequency of 0.01Hz. 0.001HZ A higher |Z| value indicates better shielding performance and durability of the coating.
[0059] The results are shown in Table 1: Table 1 Performance Test Results of Acrylic Polyurethane Coatings for Marine Corrosion Protection 1000h salt spray corrosion spread width / mm 1.5 1.3 1.2 2.7 3.2 2.1 1.9 2.4 Adhesion / MPa 7.8 8.2 8.5 6.3 5.8 5.2 7.2 6.8 <![CDATA[|Z| 0.001HZ / Ω·cm 2 ]]> <![CDATA[1.2×10 10 ]]> <![CDATA[1.5×10 10 ]]> <![CDATA[1.8×10 10 ]]> <![CDATA[6.5×10 8 ]]> <![CDATA[3.2×10 8 ]]> <![CDATA[2.1×10 8 ]]> <![CDATA[4.5×10 9 ]]> <![CDATA[3.5×10 9 ]]> As can be seen from Table 1, Examples 1-3 are significantly better than Comparative Examples 1-5 in terms of salt spray corrosion propagation width, adhesion and low-frequency impedance modulus.
[0060] In Comparative Example 1, without the addition of lanthanum nitrate hexahydrate, the salt spray resistance, adhesion, and electrochemical impedance all decreased significantly. This may be because the absence of lanthanum ions reduces the positive charge density of the hydrotalcite layer, significantly weakening its electrostatic attraction and exchange trapping ability for corrosive chloride ions. Simultaneously, lanthanum itself has corrosion-inhibiting and passivating properties; its absence prevents the formation of a dense oxide film protective layer on the metal surface, allowing corrosive media to penetrate the coating more easily. Furthermore, changes in the layer charge also affect the deposition efficiency and coating uniformity of polydopamine, indirectly reducing the interfacial bonding strength.
[0061] Comparative Example 2, which did not include gallic acid solution, showed the most severe deterioration in all its properties. This is likely because the gallate anions failed to insert into the interlayer of the hydrotalcite, resulting in an ineffective expansion of the interlayer spacing and a sharp decrease in the exchange capacity and selectivity of the hydrotalcite for chloride ions. More importantly, the absence of the pyrogallol structure inherent in gallate itself is a significant factor. These groups can act as metal chelating agents to form a passivating film and can also slowly release to inhibit corrosion in corrosive environments. Furthermore, the unintercalated hydrotalcite surface is more hydrophilic, leading to poor compatibility with subsequent polydopamine and resin matrices, and causing filler agglomeration, resulting in decreased coating density.
[0062] In Comparative Example 3, without step S2 and without polydopamine coating, the adhesion decreased most significantly, and the salt spray resistance and impedance performance also deteriorated markedly. This may be because the lack of a polydopamine coating layer means that the surface of the hydrotalcite powder lacks active functional groups such as catechol and quinone groups, which cannot form hydrogen bonds or covalent bonds with the amino groups on the surface of the aminated carbonized composite powder. As a result, the two fillers are difficult to disperse evenly during grinding and coating formulation, leading to severe agglomeration, forming microscopic stress concentration points and penetrating pores, which become rapid diffusion channels for corrosive media. At the same time, the filler and the resin matrix are only physically interlocked, with extremely weak interfacial bonding.
[0063] In Comparative Example 4, step S3 did not include tannic acid. Although its performance was better than the previous three comparative examples, it was still significantly lower than the Example. This may be because tannic acid, as a polyphenol co-carbonizing agent, reduces the number of phenolic hydroxyl groups on the surface of the carbonized composite powder, weakening the multiple hydrogen bonds and π-π stacking effects between the carbon layer and the polydopamine coating layer. This results in insufficient interfacial bonding strength between the carbon layer and polydopamine, causing some of the carbonized layer to peel off during grinding or film formation. Simultaneously, tannic acid can regulate the microporous structure and defect density of the carbon layer; its absence makes the carbon layer loose or discontinuous, reducing its physical shielding effect against chloride ions and water.
[0064] In Comparative Example 5, without step S3, commercially available attapulgite was used directly to replace the aminated carbonized composite powder. Its salt spray resistance, adhesion, and impedance performance were significantly lower than those of the examples. This is likely because the original attapulgite, without hydrothermal carbonization and amination treatment, lacks the continuous physical barrier provided by the glucose-derived carbon layer and also lacks the amino functional groups introduced by ethylenediamine. Therefore, the attapulgite rods exist only as isolated rigid particles in the coating, unable to form a covalent cross-linked network with the polydopamine-coated hydrotalcite. Agglomeration easily occurs between particles, and there are obvious gaps at the interface between the rods and the resin, allowing moisture and chloride ions to quickly penetrate along these gaps. Furthermore, the hydrophilic hydroxyl groups on the surface of the original attapulgite slightly increase the water absorption of the coating, further weakening its performance stability under long-term immersion conditions.
[0065] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing an acrylic polyurethane coating for ship corrosion protection, characterized in that, The preparation method includes the following steps: Step 1: Zinc, aluminum and lanthanum nitrates are co-precipitated with gallic acid under alkaline conditions and then hydrothermally crystallized to obtain gallic acid-intercalated zinc, aluminum and lanthanum hydrotalcite powder. Then, through oxidative self-polymerization, dopamine-coated gallic acid-intercalated zinc, aluminum and lanthanum hydrotalcite powder is obtained. Step 2: Hydrothermal carbonization and amination of attapulgite with glucose and tannic acid to obtain amination-carbonized composite powder; Step 3: Add xylene to the grinding slurry to make a composite filler slurry, and mix it with tinted paint slurry, xylene, and polyurethane curing agent to obtain an acrylic polyurethane coating for ship corrosion protection. The grinding slurry is prepared by mixing dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder, aminated carbonized composite powder, xylene and dispersant BYK-110 in a mass ratio of 180-195:90-100:180-190:5.4-6.2 and grinding to a fineness of ≤25μm.
2. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 1, characterized in that, The specific preparation method of the gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder is as follows: Under nitrogen protection, the mixed salt solution and mixed alkali solution were placed in constant pressure dropping funnels and simultaneously added to a three-necked flask using a double-drop method. The dropping rate was controlled to maintain the pH of the reaction system at 10±0.
5. After the addition was complete, the mixture was stirred in a water bath at 80-85℃ for 20-24 hours, then transferred to a high-pressure reactor and hydrothermally crystallized at 180-190℃ for 8-10 hours. After natural cooling, the mixture was filtered, and the product was washed multiple times until the filtrate was neutral. The product was then dried to constant weight to obtain gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder.
3. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 2, characterized in that, The mixed salt solution is obtained by mixing zinc nitrate hexahydrate, aluminum nitrate nonahydrate, lanthanum nitrate hexahydrate, and deionized water in a ratio of 288.2-305.4g: 165-182g: 19.14-25.36g: 2.2-2.8L. The mixed alkaline solution is obtained by mixing 13.8 wt% sodium hydroxide solution and 10.6 wt% gallic acid solution at a volume ratio of 1.1-1.3 L: 1.1-1.5 L. The volume ratio of the mixed salt solution to the mixed alkali solution is 1:
1.
4. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 1, characterized in that, The specific preparation method of the dopamine-coated gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder is as follows: Gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder was added to Tris-HCl buffer at pH 8.5, sonicated for 15-25 min, dopamine hydrochloride was added, stirred for 24-26 h, filtered, the product was washed, and vacuum dried to constant weight to obtain dopamine-coated gallic acid-intercalated zinc-aluminum-lanthanum hydrotalcite powder.
5. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 4, characterized in that, The ratio of gallic acid intercalated zinc aluminum lanthanum hydrotalcite powder, Tris-HCl buffer, and dopamine hydrochloride is 180-200g: 18-19.5L: 18-22g.
6. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 1, characterized in that, The specific preparation method of the aminated carbonized composite powder is as follows: Add attapulgite, glucose and tannic acid to deionized water, sonicate for 15-25 min, add ethylenediamine dropwise under stirring to adjust the pH to 11, transfer to a high-pressure reactor, hydrothermally react at 180-190℃ for 48-50 h, cool naturally to room temperature, centrifuge and filter, wash the product, dry it to constant weight by forced air, grind and sieve to obtain aminated carbonized composite powder. The ratio of attapulgite, glucose, tannic acid and deionized water is 90-100g: 270-280g: 45-50g: 4.5-5.2L.
7. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 1, characterized in that, The specific preparation method of the composite filler slurry is as follows: Add xylene to the grinding slurry, stir for 10-20 minutes, filter and discharge to obtain composite filler slurry; The mass ratio of xylene to grinding slurry is 184.6-196.4:455.4-491.
2.
8. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 7, characterized in that, The specific preparation method of the acrylic polyurethane coating for ship corrosion protection is as follows: Add xylene to the tinted paint slurry to adjust the viscosity to 100±5KU at 25℃, pass it through a 200-mesh sieve to obtain the main paint. Before use, add polyurethane curing agent and stir evenly to obtain an acrylic polyurethane coating for ship corrosion protection. The mass ratio of the tinted paint paste, xylene, and polyurethane curing agent is 990-1026:10-14:200-210.
9. The method for preparing an acrylic polyurethane coating for ship corrosion protection according to claim 7, characterized in that, The tinted paint paste is prepared by mixing xylene, hydroxyl acrylic resin, white paste, composite filler paste, 3-5g dispersant BYK2150, black paste, medium yellow paste and blue paste in a mass ratio of 17-21:130-135:200-215:640-650:3-5:0.3-0.5:0.1-0.18:0.05-0.
1.
10. An acrylic polyurethane coating for ship corrosion protection, characterized in that, It is prepared by the method for preparing an acrylic polyurethane coating for ship corrosion protection as described in any one of claims 1-9.
Citation Information
Patent Citations
Acrylic polyurethane coating containing modified graphene and preparation method thereof
CN121271400A
